High Levels of Transmitted HIV Drug Resistance in a Study in Papua New Guinea. - Evelyn Lavu; Ellan Kave; Euodia Mosoro; Jessica Markby; Eman Aleksic; Janet Gare; Imogen A Elsum; Gideon Nano; Petronia Kaima; Nick Dala; Anup Gurung; Silvia Bertagnolio; et al. (PLoS ONE, 2017)
Introduction Papua New Guinea is a Pacific Island nation of 7.3 million people with an estimated HIV prevalence of 0.8%. ART initiation and monitoring are guided by clinical staging and CD4 cell counts, when available. Little is known about levels of transmitted HIV drug resistance in recently infected individuals in Papua New Guinea. Methods Surveillance of transmitted HIV drug resistance in a total of 123 individuals recently infected with HIV and aged less than 30 years was implemented in Port Moresby (n = 62) and Mount Hagen (n = 61) during the period May 2013-April 2014. HIV drug resistance testing was performed using dried blood spots. Transmitted HIV drug resistance was defined by the presence of one or more drug resistance mutations as defined by the World Health Organization surveillance drug resistance mutations list. Results The prevalence of non-nucleoside reverse transcriptase inhibitor transmitted HIV drug resistance was 16.1% (95% CI 8.8%-27.4%) and 8.2% (95% CI 3.2%-18.2%) in Port Moresby and Mount Hagen, respectively. The prevalence of nucleoside reverse transcriptase inhibitor transmitted HIV drug resistance was 3.2% (95% CI 0.2%-11.7%) and 3.3% (95% CI 0.2%-11.8%) in Port Moresby and Mount Hagen, respectively. No protease inhibitor transmitted HIV drug resistance was observed. Conclusions The level of non-nucleoside reverse transcriptase inhibitor drug resistance in antiretroviral drug naïve individuals recently infected with HIV in Port Moresby is amongst the highest reported globally. This alarming level of transmitted HIV drug resistance in a young sexually active population threatens to limit the on-going effective use of NNRTIs as a component of first-line ART in Papua New Guinea. To support the choice of nationally recommended first-line antiretroviral therapy, representative surveillance of HIV drug resistance among antiretroviral therapy initiators in Papua New Guinea should be urgently implemented.